Emergency Separation Simulation and Damage Prediction of an Airliner under Wheel-Up Landing Condition - Pengfei Zhang; Hong Nie; Jianfei Wu; Muqi Yu (Shock and Vibration)
To predict the damage to and response of aircraft structures during wheel-up crash landing, numerical simulations were performed using a constitutive and damage model for ductile metallic materials developed in the ABAQUS/Explicit environment. The model of an entire aircraft and detailed submodels were established. The Johnson–Cook and Gurson material constitutive models were validated by conducting Hopkinson’s bar test. A drop hammer test and a static test of the fuse pins were performed to determine and verify the response and strength of the structure. The experimental and analytical results indicate that the stain rate and damage parameters significantly influence the emergency separation load, fuse pin strength, and separation sequence. The analysis results were compared with the test results, and a close agreement was found in terms of the maximum load and deformation.